The correlation between calcaneocuboid joint involvement and sustentacular fragment displacement among male patients with displaced intra-articular calcaneal fractures - Wenchuang Fan; Haining Zuo; Xing Lu; Xinglin Zhang; Zhiyong Zhou; Chuanqiang Jiang (Scientific Reports)
Abstract Sustentacular fragment displacement is not uncommon in calcaneal fractures. The factors that suggest a possible displacement of sustentacular fragment are still unclear. Displaced intra-articular calcaneal fractures with calcaneocuboid joint involvement are the most common type of calcaneal fracture. The purpose of this study is to investigate whether there is a correlation between calcaneocuboid joint involvement and sustentacular fragment displacement in displaced intra-articular calcaneal fractures. We collected basic data and CT scans of male patients with displaced intra-articular calcaneal fractures who were hospitalized in the north district of our hospital from July 2021 to June 2024. Three different logistic regression models were employed to analyze the relationship between calcaneocuboid joint involvement and sustentacular fragment displacement. Additionally, stratification analyses and their interactions were further carried out. 144 calcaneal fractures in 131 male patients were included in our study. 63 cases, accounting for 43.75%, exhibited sustentacular fragment displacement. In logistic regression analysis, a favorable association was noted between calcaneocuboid joint involvement and sustentacular fragment displacement (OR = 2.33, 95% CI: 1.18–4.59, P < 0.05). In model 2, the association retained statistical significance after adjusting for confounding factor (OR = 2.27, 95% CI: 1.15–4.51, P < 0.05). In model 3, further adjustment for all potential confounding factors also showed a statistically significant association (OR = 2.31, 95% CI: 1.14–4.68, P < 0.05).Similar results were obtained in stratified analyses. Among male patients with displaced intra-articular calcaneal fractures, it was initially discovered that calcaneocuboid joint involvement can significantly increase the risk of sustentacular fragment displacement, particularly in Sanders type 3 and 4 fractures and when the proportion of the posterior facet in sustentacular fragment is less than 50%.